A New Index of the Business Environment for Microfinance - Cull, Robert; Navajas, Sergio; Nishida, Ippei; Zeiler, Renate (Elsevier, 2015)
This paper describes a new index of the quality of the business environment for microfinance institutions (the Global Microscope on the Microfinance Business Environment). Regressions are used to validate the index by linking it and its sub-components to microfinance outcomes. The main findings are that the components of the index related to the supporting institutional framework are strongly linked to measures of microfinance penetration (such as microfinance borrowers as a share of total population). Components related to the framework for regulation and supervision are more strongly linked to outcomes at the MFI level, including loan portfolio quality, financial self-sufficiency, average loan size, and the share of lending to women. Many, but not all, of these relationships are robust to using instrumental variables estimation in which a country’s general stringency with respect to financial regulation is used as an instrument for the index and its components.